Napływ kapitału niemieckiego do Polski i jego rozmieszczenie na Dolnym Śląsku (1989-2004) - Popławski, Maciej (The German Capital Inflow Process to Poland and its Location in Lower Silesia (1989-2004), 2006)
The article presents the German foreign direct investments inflow process to Poland the background of other countries investments during the transformation process. The structure of the foreign capital in Poland and in Lower Silesia was presented (according to the origin country at the end of the particular stage in millions USD). The process of Ike German foreign direct investments inflow to Lower Silesia during the transformation process was shown for the Jeleniogórsko-Wałbrzyski, Legnicki and Wrocławski subre-gions, (1989-1998) as well as Lower Silesia voivodship (1999-2004).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 158-171